Environmentally derived subgroups of preadolescents with family history of substance use exhibit distinct patterns of psychopathology and reward-related behaviors: insights from the ABCD study - Ramakrishnan, Srinivasan A.; Shaik, Riaz B.; Peri, Siddhartha; Adams, Faith; Haas, Shalaila S.; Frangou, Sophia; Srinivasan, Shankar; El-Shahawy, Omar; Hammond, Christopher J.; Ivanov, Iliyan; Parvaz, Muhammad A. (Frontiers in Child and Adolescent Psychiatry, 2025)
BackgroundFamily history of substance use (FHSU), along with sociodemographic and psychosocial factors, has been identified as a key risk factor for adolescent substance use and progression to substance use disorders (SUD). However, the interaction between distinct sociodemographic and psychosocial profiles in adolescents with FHSU and constitutional factors, such as psychopathological symptom severity, impulsivity, and reward processing, remains unclear. Given the complexity of these factors, it is crucial to explore how these elements contribute to the differential vulnerability to SUD among youth with family history of substance use. Particularly as, the identification of clinically relevant subgroups of at-risk youth may inform precision prevention and treatment approaches to reduce adverse outcomes related to SUDs.MethodsHere, we used data from the Adolescent Brain Cognitive Development (ABCD) study and grouped the participants (age: 9–10 years) into positive and negative FHSU [i.e., FHSU-P (n = 1955; female 49.7%, White 57.95%), and FHSU-N (n = 4,369; female 48.33%, White 61.16%), respectively]. We used K-means clustering to identify latent subgroups in the FHSU-P population based on psychosocial variables and then compared the resulting subgroups on internalizing, externalizing, and total psychopathology, impulsivity, and reward prediction errors.ResultsK-means clustering revealed five subgroups within FHSU-P: Subgroups 1 (n = 744) and 2 (n = 300) exhibited favorable psychosocial profiles, marked by higher school involvement, social engagement, and parental acceptance. Subgroups 3 (n = 267), 4 (n = 201), and 5 (n = 443) were characterized by lower engagement across peer, school, and parental domains. Group comparisons showed that Subgroups 1 and 2 had comparable levels of psychopathology and impulsivity, while Subgroups 3, 4, and 5 displayed higher psychopathology and impulsivity. Reward prediction errors were similar across all subgroups. Other group differences are also presented and discussed in the main text.ConclusionThese findings highlight significant heterogeneity within the FHSU-P group and emphasize the importance of stratifying adolescents based on sociodemographic and psychosocial factors. Such stratification can help identify adolescents at higher risk for psychopathologies, including SUDs, offering insights for targeted prevention and intervention strategies.